The memoirs of Ceija Stojka, child survivor of the Romani Holocaust - Stojka, Ceija (Women and gender in German studies., 2022)
""Is this the whole world?" This question begins the first of three memoirs by Austrian Romani writer, visual artist, musician, and activist Ceija Stojka (1933-2013), told from her perspective as a child interned in three Nazi concentration camps from age nine to 15. Written by a child survivor much later in life, the memoirs offer insights into the nexus of narrative and extreme trauma, expressing the full spectrum of human emotions: fear and sorrow at losing loved ones; joy and relief when reconnecting with family and friends; desire to preserve some memories while attempting to erase others; horror at acts of genocide, and hope arising from dreams of survival. In addition to annotated translations of the three memoirs, the book includes two of Stojka's poems and an interview as well as color reproductions of several of her artworks and historical photographs from her family records. An introduction contextualizes her works within Romani history and culture, and a glossary informs the reader about the "concentrationary universe." Because the memoirs show how Stojka navigated male-dominated postwar Austrian culture, generally discriminatory to Roma, and the patriarchal aspects of Romani culture itself, the book is a contribution not only to Holocaust Studies but also to Austrian Studies, Romani Studies, and Women's and Gender Studies"--